Análisis de contenido en investigación pedagógica en educación física: Estudio sobre la práctica curricular curricular supervisada - Benites, Larissa Cerignoni [UNESP]; Do Nascimento, Juarez Vieira; Milistetd, Michel; Farias, Gelcemar Oliveira (My University, 2016)
This article is a step-by-step description of a study on teacher training in the context of curricular supervised internship in Physical Education. Using Bardin’s (1979) content analysis procedures – pre-analysis, exploration of material, result processing, inference, and interpretation – it describes in detail the pathway adopted by researchers in the process of understanding the dialogue between school, assistant teacher, and student.
Análise de conteúdo na investigação pedagógica em educação física: Estudo sobre estágio curricular supervisionado
Content analysis in educational research in physical education: A study on curricular internship
Keywords: Internship; Qualitative research; Teachers; Teaching